STUDENTS’ ERRORS IN USING COORDINATING CONJUNCTIONS AT ELEVENTH GRADE STUDENTS - Imam Ahmad Ma’shum (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
In constructing sentences, it needs a connector or it can be called conjunction. It is important that a writer must master. The use of conjunctions also had many portion in meaning of the sentences. In this case, the students are able to understand what the conjunction is. Then they are able to construct the correct one. This study focused on the students’ errors in using the conjunction. They are Indonesian students that still learning about the second language, especially English. An error also done in several times, this is because they can’t master the conjunction itself, and using it. Then they construct the sentences with less understand of constructing sentences, especially in using the connector or the conjunction. In line with Richards (1971) the errors come from 3, those are Interference Error, Intralingual Error, and Developmental Error. Based on the result, the students’ errors are coming from Intralingual Errors, also Developmental Errors. The students may use the conjunction with the wrong formula or can be from their lack of knowledge also less in vocabularies. This study analyzed the students that in eleventh grade in senior high school. This study used 2 instruments, that was test also interview that validated to an expert that mastering language testing. The analysis of students’ error be descriptively analyzed, so it used Qualitative Descriptive method. The Result proved that students still using coordinating conjunctions except ‘for’ incorrectly. The errors were coming from intralingual errors, and developmental errors.